Adaptive Governance Strategy to Reduce Flood Risk in the Ganges River, North India - Khant Banhi (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This take a look at examines the dynamics of flood chance perception, adaptive governance effectiveness, and community resilience along the Ganges River in North India, focusing on the village of Kalapathar. Subjects and Methods: Through regression, ANCOVA, and correlational analyses, the studies explore the relationships between these key variables and their implications for flood resilience strategies. Results: Findings highlight the great impact of flood chance notion on community resilience and the high-quality correlation among adaptive governance effectiveness and resilience. Conclusions: The take a look at underscores the significance of addressing perceptions of chance, enhancing governance mechanisms, and fostering community resilience to mitigate flood affects in prone regions.